MiRNA‐221 and miRNA‐222 induce apoptosis via the KIT/AKT signalling pathway in gastrointestinal stromal tumours. Issue 7 (10th April 2015) - Ihle, Michaela Angelika; Trautmann, Marcel; Kuenstlinger, Helen; Huss, Sebastian; Heydt, Carina; Fassunke, Jana; Wardelmann, Eva; Bauer, Sebastian; Schildhaus, Hans-Ulrich; Buettner, Reinhard; Merkelbach-Bruse, Sabine
Abstract : Aberrantly expressed microRNAs (miRNAs) are involved in many diseases including cancer. In gastrointestinal stromal tumours (GISTs) expression of miR‐221 and miR‐222 is reduced compared to control tissue and other sarcomas but the functional effects of this downregulation are not fully understood. This study aimed at evaluating the miR‐221 and miR‐222 expression profiles in different GIST subtypes and the functional role of these miRNAs. Expression of miR‐221 and miR‐222 was analysed in six KIT exon 9 and three KIT exon 11 mutated and nine wildtype GISTs by qPCR. Viability and apoptosis were examined in three different, KIT positive GIST cell lines (GIST882, GIST‐T1 and GIST48) after overexpression of these miRNAs. The modulation of KIT and the PI3K/AKT pathways was determined by Western blot. Wildtype and KIT mutated GISTs revealed reduced miRNA expression compared to adequate control tissue. miRNA expression was lower for wildtype compared to mutated GISTs. Transient transfection of miR‐221 and miR‐222 reduced viability and induced apoptosis by inhibition of KIT expression and its phosphorylation and activation of caspases 3 and 7 in all three GIST cell lines. p‐AKT, AKT and BCL2 expression was reduced after miRNA transfection whereas only slight influence on p‐MTOR, MTOR and BCL2L11 (BIM) was detected. Our results demonstrate that miR‐221 and miR‐222 which are downregulated in wildtype and mutated GISTs, induce apoptosis in vitro by a signalling cascade involving KIT, AKT and BCL2. Therefore, overexpression of these miRNAs seems to functionally counteract oncogenic signalling pathways in GIST. Highlights: miR‐221 and miR‐222 are downregulated in GIST. Overexpression of miR‐221 and miR‐222 reduce cellular proliferation. This antiproliferative effect correlated with an induction of apoptosis. Induction of apoptosis is mediated by a signaling cascade involving KIT, AKT and BCL2.